Efeitos da inundação sobre o manejo da pecuária no Pantanal norte com emprego de imagens orbitais - Alves, Gustavo Benedito Medeiros (2015)
Cattle ranching is the main economic activity in the Brazilian Pantanal, managed according to the hydrological regime. Flood events are part of the dynamics of life of the rancher in this region, but they are poorly understood and can cause economic losses. In this way, the present study analyzed the spatial and temporal dynamics of floods in a region (15º42’27”/16º48’52”S and 55º2’2”/56º0’17” W) in northern Pantanal and its influence on cattle ranching management. TOPODATA image (30m) was used for extraction of drainages and identification of areas subject to flooding. The quota values up to 200 m were correlated with the Land Surface Water Index (LSWI) of MOD13Q1 images, considering the flood pulse from 2008 to 2014. A logistic regression model was developed to validate the performance of LSWI indistinguishing flooded areas. From the results of LSWI, MODIS images from 2010 to 2012 were selected to analyze the Normalized Difference Vegetation Index (NDVI), in order to detect the development of vegetation, according to the phases of the flood pulse. Ranchers and locals were interviewed to gather information to understand the cattle management processes, assess the results of the indices and the flood maps. LSWI showed a 96% efficiency for analysis of flooded areas; the plain (753.328 ha) may flood up to 66.7% of its total area. The largest average area flooded (46.3%) was observed in 2014 and the smallest (30.6%), in 2012. NDVI indicated that the hydrological phases interfere with the distribution of vegetation, so that, in the low water period, up to 81% of the floodplain area has potential to be used as pastures and in the high water period, this area is reduced to 30%. Livestock management follows the availability of forage and can be conducted in the farm itself, or with displacement between low- and highlands. LSWI allowed the identification of areas prone to flooding in the Pantanal and NDVI enabled to relate the availability of pastures to cattle in the different hydrological phases. The analysis of flood processes has proven essential to understanding the traditional livestock management. This production model is closely related to variations in rainfall, relief, flow and direction of water on the plain, and especially the alternation of low and high water phases in the Pantanal.